2018
DOI: 10.21608/jpp.2018.36637
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foliar Application with Micronutrients under Different Fertilizer Levels on Cotton Cultivar Giza 94

Abstract: Two field experiments were carried out in Sakha Agricultural Research Station at Kafr El-Sheikh Governorate, Egypt, during the growing seasons 2016 and 2017 to study the effect of foliar application with micronutrients under different NPK fertilizer levels on growth, earliness, yield and its components and fiber traits of cotton on the cotton cultivar (Giza 94) belonging to (Gossypium barbadense, L). Each experiment was laid out in a split plot design with four replications. The main plots were allocated to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Significant raise in plant height was observed by the application of boron and zinc which might be due auxin biosynthesis leading to cell elongation [12]. It also has been reported that high levels of NPK and different micronutrients played a significant role in plant height [13].…”
Section: Resultsmentioning
confidence: 99%
“…Significant raise in plant height was observed by the application of boron and zinc which might be due auxin biosynthesis leading to cell elongation [12]. It also has been reported that high levels of NPK and different micronutrients played a significant role in plant height [13].…”
Section: Resultsmentioning
confidence: 99%